ASPEK PEMBIAYAAN HUTANG MENURUT SYEIKH DAUD AL-FATANI DALAM FURŪ‘ AL-MASĀ’IL: Debt Financing Aspect According to Sheikh Daud al-Fatani in Furū‘ al-Masā’il - Towpek, Hadenan (Jurnal Syariah, 2017)
Furū‘ al-Masā’il is a popular work by the prolific Malay scholar, Sheikh Daud al-Fatani (1131-1265H/1718-1847M). It is also considered a masterpiece written during a prominent period in fiqh discipline which includes fiqh al-mu‘āmalāt; being directly related to the economic and finance fields. This article scrutinizes debt financing aspect as perceived indirectly by the author in the mu‘āmalāt chapter. This article applies a literary critical method known as taḥqīq al-nuṣūṣ. It was found that debt financing can be identified under four (4) subtopics of contract: al-salam, al-ijārah, al-qarḍ and al-murābaḥah. It also points out that debt financing is relevant to the practice in Malaysian Islamic banking. This particular relevancy can be summarized into two main aspects: aspect of definition and aspect of application. In addition, this article also illustrates that with some modifications in preparing debt financing concepts in accordance to Sheikh Daud’s views, the practice will become more Shariah compliant as well as more practical.